Measuring Supply Chain Performance of Broiler Distributors and Producers Using SCOR and AHP Methods - Oktaviani Rahmah Marddani; Syarif Hidayatuloh; Reza Ardiansyah Teguh Saputro; Khasbi Niami (Telkom University, 2025)
CV. Sinar Pangan Mandiri is an industry engaged in the distribution and producers of broiler chickens. The company faces several problems, including a manual bookkeeping system and constrains related to long and time-consuming transportation distances that will have an impact on overall supply chain performance. CV. Sinar Pangan Mandiri has never conducted a performance measurement of its supply chain. Supply chain performance measurement is applied to assess the quality of the company’s supply chain, encourage implementation to evaluate the quality and efficiency of the supply chain, and identify potencial improvements that can increase the company’s competitiveness. In this research, the SCOR 12.0 model and AHP (Analitycal Hierarchy Process) methods were used. The results of the supply chain performance measurement obtained an average value of 85.25, falling into the good category. Further analysis of each SCOR core process at level 1, namely plan, source, make, and deliver, obtained performance values of 70.01, 100, 82.17, and 84.44, respectively. Thus, it can be concluded that the highest performance is in the source process, while the lowest performance is in the plan process. From these indicators, it shows that the supply chain process at CV Sinar Pangan Mandiri requires improvement in several processes.